L2 Pragmatic Competence in Chinese Secondary Schools - Teaching: Approaches, Teaching Materials, and Classroom-Based Assessment (Asian Education Studies, 2019)
English as a L2 (second language) is compulsory in many countries’ education. However, the pragmatic competence is far less developed, compared with the grammatical competence. This situation leads to a fact that many students are confident in grammar-oriented tests, but afraid of starting a conversation. Or, in many cases, the students may bewilder the native speakers. This paper concerns the teachability of L2 (Second Language) pragmatic competence in Chinese secondary schools. It starts with a relatively comprehensive introduction of some very basic concepts, including pragmatics, pragmatic competence, and ILP (interlanguage pragmatics). Next, the necessity of consciously learning of L2 pragmatic competence is discussed within the specific context, as well as its teachability. After that, challenges of L2 pragmatic competence teaching are raised from three aspects: 1) challenges for teachers in the teaching process; 2) lack of authentic L2 pragmatic input; and 3) the testing and assessment of L2 pragmatic competence. Finally, feasible ways to facilitate the teaching application of L2 pragmatic competence are proposed.